Forecasting the Cold Chain Logistics Demand for Fresh Agricultural Products in China - Yuanyuan, Chen (UNIMAS, 2024)
Due to improved living standards and a growing emphasis on health, fresh agricultural products have become integral to our daily diets. This trend is primarily attributed to their high protein content and abundant supply of essential vitamins. However, the perishable nature of these goods underscores the critical importance of cold chain logistics, which has the potential to significantly mitigate product deterioration. Presently, the coverage of cold chain logistics in China lags behind that of industrialized nations, resulting in a mismatch between supply and demand. Moreover, outdated technology and a shortage of skilled professionals further exacerbate this disparity. China’s diverse geographical landscape and varied lifestyles influence the various demands for cold chain logistics. This study employed a static panel data model to investigate the factors influencing the demand for cold chain logistics for fresh agricultural products, both in coastal and inland regions. The key determinants in China identified include the value added of the primary industry, freight turnover, ownership of civilian goods vehicles, internet broadband access subscribers, and the impact of COVID-19. Value added of the primary industry, ownership of civilian goods vehicles, internet broadband access subscribers, and the COVID-19 pandemic were a few factors that primarily affect coastal regions. On the other hand, the effects of COVID-19, the value added of the primary industry, freight turnover, ownership of civilian goods vehicles, and internet broadband access subscribers were what drive inland areas. Based on these findings, specific development recommendations were proposed for cold chain logistics in different regions of China, aiming to provide theoretical support for advancing the industry. Then, utilizing the GM (1,1) model, future demand for cold chain logistics in fresh agricultural products was forecasted for the next five years, encompassing China as a whole as well as its coastal and inland regions. Projections indicated that by 2027, the demand for iii iv cold chain logistics for fresh agricultural products in China is expected to reach 1,571.14 million tons, with 694.58 million tons in coastal areas and 876.56 million tons in inland regions. These insights were instrumental in facilitating informed investment strategies in cold chain logistics and formulating relevant policies to foster industry development.